India's Progress towards the health related Millennium Development Goals –HIV/AIDS - P, Patel; J, Chang; J, Srivastava; I, Patel; R, Balkrishnan (Indian Journal of Pharmacy Practice)
Controlling and reversing the spread of AIDS/HIV is the key focus of the 6 Millennium Development Goal (MDG) proposed by United Nations. One of the critical links for attaining MDG 6 targets is India. India has one of the largest populations of HIV infected individuals in the world and addressing this issue requires multidimensional, complex solutions. This paper looks at various social and economic factors contributing to the prevalence of HIV/AIDS in India. An overview of steps being taken by government and various other organizations to address the threat of HIV/AIDS is presented with particular emphasis on vulnerable populations like commercial sex workers (CSWs), injecting drug users (IDUs), men having sex with me (MSMs) and HIV positive children due to mother to child transmission (MTCT). The paper presents a brief overview of the challenges faced by the Indian government and the NGOs to combat HIV/AIDS and provides recommendations discussing issues and interventions based on economic efficiency perspective.
Keywords: HIV/AIDS; commercial sex workers; injecting drug users; MSMs; MTCT; NACO